Rodeo Thumb: To Replant or Not. Issue 3 (24th August 2021) - Davis, Justin J.; Meade, Anna E.; Cochran, Lindsey; Sammer, Douglas M.; Zhang, Andrew Y.
Abstract : Background: This study investigated patient-reported outcomes after surgical treatment of rodeo thumb amputation to guide clinical decision-making. Methods: A retrospective review was performed for rodeo thumb amputations from 2009 to 2019. Patient-reported outcomes were collected and compared by injury level, age, and treatment. Two-sided t test was used to compare continuous variables, and Pearson chi-square test was used to compare categorical data. Results: The study included 37 patients. Patients with interphalangeal injuries treated with replantation had Quick Disabilities of the Arm, Shoulder and Hand questionnaire scores similar to those treated with amputation (1 versus 8; p = 0.07). There was no significant difference in percentage of patients with similar or better roping ability after treatment (40 percent versus 79 percent; p = 0.26), and similar percentages were satisfied (80 percent versus 71 percent; p = 1.00). Patients with metacarpophalangeal injuries treated with replantation and those treated with amputation had similar questionnaire scores (7 versus 10; p = 0.47). Both groups had similar roping ability after treatment (67 percent versus 56 percent; p = 1.00), and there was no statistically significant difference in satisfaction (79 percent versus 44 percent; p = 0.34). Pediatric patients had questionnaire scores similar to those of adults (6 versus 8; p = 0.42). A significantly higher percentage of pediatric patients had similar roping ability following injury than adults (100 percent versus 54 percent; p = 0.02). Most patients in both groups were satisfied (89 percent versus 61 percent; p = 0.22). Conclusions: For both interphalangeal and metacarpophalangeal injuries, patient-reported outcomes were similar regardless of treatment. Children were able to return to roping and perform at a similar or higher level at a greater rate than adults, but had similar questionnaire scores and satisfaction.